The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/cdoe.12522
|View full text |Cite
|
Sign up to set email alerts
|

Depression, drugs and dental anxiety in prisons: A mediation model explaining dental decay experience

Abstract: Objective:To test a theoretical mediation model and investigate whether drug use and/or dental anxiety act as mediating factors between depression and dental decay experience among prisoners. Method:A cross-sectional survey was conducted on a convenience sample of 300 prisoners across three prison establishments in Scotland. Depression and dental anxiety were measured using the Centre for Epidemiological Studies Depression Scale and the Modified Dental Anxiety Scale, respectively. Drug use was assessed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…The data collected in the study by Arora et al [ 33 ] in prisons in Scotland demonstrated the comorbidity relationship between mental health and oral health and demonstrated the importance of incorporating oral health policy into prison and inclusion of oral health promotion measures to ensure that these needs are more adequately met, reducing impacts on the quality of life of these prisoners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data collected in the study by Arora et al [ 33 ] in prisons in Scotland demonstrated the comorbidity relationship between mental health and oral health and demonstrated the importance of incorporating oral health policy into prison and inclusion of oral health promotion measures to ensure that these needs are more adequately met, reducing impacts on the quality of life of these prisoners.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of people with mental health problems in prisons in the United States was identified three times more frequently than in US hospitals [ 33 ]. Also in this regard, a study carried out in Scottish prisons found that the prevalence of depressed individuals in these environments is double that in the Scottish population [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, stress and depression can be considered as confounders because are associated with BMI 21 and with dental caries 12 and can be considered mediators because a decrease of BMI can decrease the risk of depression 22,23 and depression could influence tooth loss 24 (Figure 1). Therefore, we excluded behavioral variables from the second analysis considering this possibility.…”
Section: Confounding/mediator Variablesmentioning
confidence: 99%
“…Nýleg rannsókn meðal skoskra fanga fjallað m.a. um hversu flókið orsakasamhengið getur verið (39). Rannsóknin gaf til kynna tvaer samhliða og sjálfstaeðar millibreytur, vímuefnanotkun og tannlaeknafaelni.…”
Section: Vímuefnamisnotkun Og Tannheilsaunclassified